دراسة أعطال صمامات العادم لبعض المحركات الرئيسية في سفن الشحن التجارية - شلوف, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
يعتبر حصول أعطال مفاجئة في سفينة مبحرة إما سبباً أو مقدمة لكارثة إنسانية واقتصادية وبيئية، لذلك فإن دراسة أسباب الأعطال تمثل خطوة مهمة في تفادي حصول تلك الأعطال. لقد بينت الدراسات أن أخطر الأعطال تلك التي تحدث في المحرك الرئيسي أثناء الإبحار في الظروف البحرية والجوية السيئة، كما بينت أن أعطال صمامات العادم في المحركات الرئيسية ذات الكسح الطولي هي الأكثر حدوثاً، حيث يرتفع تواتر حصولها في هذه الأنواع من المحركات. قمنا في هذا البحث بدراسة تلك الأعطال وتجميع معطيات تمت معالجتها لاحقاً، وتوصلنا إلى مجموعة من النتائج التي نرى أن وضعها في يد المستثمرين سيكون ذا فائدة كبيرة في تفادي حصول الأعطال المشار إليها، ومن ثم تفادي أو التقليل من حوادث السفن الناتجة عنها. The sudden failures in a sailing ship are considered either a cause or an introduction to a humanitarian, economic and environmental catastrophe. Therefore, studying the reasons which cause these failures are an important step in avoiding them. Studies have shown that the most serious failures are those that occur in the main engine while sailing in poor sea and weather conditions. They have also shown that exhaust valves' failures in main engines with uniflow-scavenge are the most frequent, as their occurrences become more likely in these types of engines. In this research we have studied these failures, gathered data which were later processed. And we have reached a group of conclusions that we see that placing them in the hands of the operators will be of immense benefit in avoiding the above mentioned failures, and consequently help avoiding and reducing the resultant accidents.